Internet Usage by Adolescents Implication on their Studies and Academic Performance - Mukhia, Arati; K., Saileela; Kujur, Donatus (JOURNAL OF INDIAN EDUCATION, 2020)
Educationists and researchers have been constantly investigating the effects of media and technologies such as the Internet, on the psycho-social behaviour of adolescents. Moreover, recent studies conducted suggest that the use of the Internet impact the academic performance of students. This paper aims to explore the effects of Internet usage on higher secondary school students’ academic performance. To collect data, a personal information form, and an Internet Usage Scale developed by the authors were applied to 511 students from 11 different schools of Darjeeling district. Results revealed that the time spent online was found to be associated with academic performance while Internet usage did not correlate very well to academic scores. Family demographics did not play any role on Internet Usage.